Basement Regions - Godard, Alain; Lagasquie, Jean-Jacques; Lageat, Yannick (Springer Berlin Heidelberg, 2001)
The basement regions constitute more than two-thirds of outcropping bedrock material across our planet's continents. During the past 30 years French geomorphologists have contributed greatly to the characterization of some of the laws and patterns of landform evolution in shields and crystaliine areas with changing bioclimatic environments. This volume reflects the search for a better understanding of landscapes and landforms in igneous and metamorphic terrains at different latitudes. Furthermore, it covers a wide field of investigation gathered on four continents and addresses the issue at a wide range of spatial and timescales. It is an ideal volume not only for post-graduate geomorphology students but also for geoscience scholars concerned with igneous petrology, quaternary geology, physical geography, soil science and land use planning